Phytochemical Constituent and Antioxidant Activity Evaluation of Red Seaweed Eucheuma sp. - Arsianti, Ade (Indonesian Journal of Medical Chemistry and Bioinformatics, 2023)
Oxidative stress is a condition in which there is an imbalance between production of free radicals and protective response via antioxidant system. There are endogenous and exogenous antioxidants, however as age increases, there is a reduction in endogenous antioxidant, thus the search for potential exogenous antioxidants which could be derived from natural resources are needed. Indonesia is a megabiodiversity country which has more than 30,000 species of plants and animals. Red seaweed Eucheuma sp. is one of marine macroalgae species which shows potent biological activities. This study aims to determine the phytochemical constituent and to evaluate the antioxidant activity of red algae Eucheuma sp. Seaweed Eucheuma sp. obtained from Lombok, Nusa Tenggara Barat, Indonesia, were extracted by maceration process using three solvents, n-hexane, ethyl acetate, and ethanol, sequentially. Each extract was analyzed for its phytochemical constituents by phytochemistry screening, thin layer chromatography, total phenolic content, total flavonoid content, and total triterpenoid content. Evaluation of antioxidant activity for ethyl acetate extract and ethanol extract were done using DPPH method. Phytochemical analysis of Eucheuma sp. shows positive result for steroid and triterpenoid. Thin layer chromatography analysis of the Eucheuma sp. extracts showed total of 11 phytochemical constituents. Quantitative analysis revealed that the highest value in ethyl acetate extract, with total phenolic content of 29.57 mg gallic acid equivalent/g extract, total flavonoid content of 0.54 mg quercetin equivalent/g extract, and total triterpenoid content of 1.08 mg ursolic acid equivalent/g extract. Moreover, ethylacetate extract of Eucheuma sp. demonstrated an active antioxidant activity against DPPH free radical with IC50 value of 27.96 µg/mL. Thus, ethylacetate extract of Eucheuma sp. derived from Lombok, Indonesia, has a potential to be developed as a natural antioxidant.